(untitled) (New York, 2006)
Williams Hematology" remains the cornerstone text in the literature for hematology. Its discrete cell-by-cell approach has always been perceived as the most readily accessible by novices and experts alike, and now it is more clinical than ever through the inclusion of new key-point boxes and algorithms that outline discrete strategies for diagnosis and treatment. Includes 800 illustrations.
Keywords: Blood,Hematology,Hematologic diseases; Diseases